The changing face of epidemiology: gender disparities in citations? - Schisterman, Enrique F (Epidemiology, 2017)
BACKGROUND: Female biomedical scientists tend to publish fewer articles as last author than their male colleagues and accrue fewer citations per publication. We seek to understand whether epidemiology follows this pattern. METHODS: We gathered aggregate information on the current gender distribution of epidemiology departments (n=29 of 71 surveyed), societies (n=4 of 8), and journal editorial boards (n=6 of 6) using two online surveys and publicly available online information. Bibliometric data from 4149 articles published between 2008–2012 in six high-impact epidemiology journals were drawn from Web of Science and PubMed. RESULTS: We observed a higher prevalence of female than male doctoral students and epidemiology faculty, particularly at lower faculty ranks. 54% of society members were female. Among editorial boards, all current and emeritus editors-in-chief were male and board membership was largely male (64%). Females were more likely to be first authors, but less likely to be last authors. There were no differences in accrued citations at the 50(th) percentile by first or last author gender. However, articles with male first and last authors tend to accrue more citations (5.7 citations, 95% CI 2.1, 9.4), mostly driven by the most highly cited articles. This disparity is not fully explained by potential confounders, including seniority. CONCLUSIONS: We found a greater number of female epidemiologists in early career positions and further evidence of potential gender disparity in publication metrics in epidemiology. If epidemiology continues to be practiced by a majority of women, it remains to be seen if these patterns will change over time.